Widely-linear minimum-mean-squared error multiple-candidate successive interference cancellation for multiple access interference and jamming suppression in direct-sequence code-division multiple-access systems - Yang, Jianwei; de Lamare, Rodrigo C (IET signal processing, 2015)
In this paper, the authors propose a widely-linear (WL) receiver structure for multiple access interference (MAI) and jamming signal (JS) suppression in direct-sequence code-division multiple-access systems. A vector space projection (VSP) scheme is also considered to cancel the JS before detecting the desired signals. They develop a novel multiple-candidate successive interference cancellation (MC-SIC) scheme which processes two consecutive user symbols at one time to process the unreliable estimates and a number of selected points serve as the feedback candidates for interference cancellation, which is effective for alleviating the effect of error propagation in the successive interference cancellation (SIC) algorithm. WL signal processing is then used to enhance the performance of the receiver in non-circular modulation scheme. By bringing together the techniques mentioned above, a novel interference suppression scheme is proposed which combines the WL MC-SIC minimum-mean-squared error (MMSE) algorithm with the VSP scheme to suppress MAI and JS simultaneously. Simulations for binary phase shift keying modulation scenarios show that the proposed structure achieves a better MAI suppression performance compared with previously reported SIC MMSE receivers at lower complexity and a superior JS suppression performance.